Assessing the Macroeconomic Impact of Structural Reforms in Ukraine - Ari, Anil (IMF Working Papers; Working Paper ;, 2021)
Ukraine's economic performance has been anemic since the early 1990s. A major impediment to productivity growth has been low investment, held back by lack of strong and independent institutions. This paper aims to assess the major areas of institutional weakness in Ukraine and quantify the long-term growth impact of catching-up to Poland in terms of the quality of major economic institutions and market development. Our analysis identifies the legal system as the area where the institutional quality is weakest compared to Poland, followed distantly by market competition, openness to trade and financial depth. Using a methodology that accounts for positive spillovers between the structural reform areas, we estimate that even under the most optimistic scenario, where institutional gaps are fully addressed, Ukraine would need 15 years to catch up to Poland's current income level.